The impacts of employees' job stress on staff's job performance at administrative office in Bahagian Samarahan, Sarawak / Norlina Mohamed Noor ... [et al.] - Mohamed Noor, Norlina; Salleh, Juliza; Abdul Rafil, Aida Nabilah; Johari, Aiza (Universiti Teknologi MARA, Perlis, 2020)
Job performance refers to an employee's proficiency to perform well in achieving goals and behaviors which involve deliberate arts that are useful to the organization. Job performance can be improved if the employees manage to handle their job stress. This study investigates the significant effects and the relationships between job stress factors and job performance among the staffs at Pejabat Residen, Bahagian Samarahan, Sarawak. This study utilizes Job Demands-Control (JDC) Model by Karasek, which focuses on job demand and job control groups. Job demand consists of two dimensions; workload and time pressure while job control incorporates skill discretion and decision authority. One hundred questionnaires were conveniently distributed, and only 91 were returned and considered usable. This study used correlation and Multiple Linear Regression (MLR) analysis using SPSS version 25. The results show that job demand, job control, workload and time pressure had a significant relationship towards job performance. When the candidates had adequate time, decision-making empowerment and task-related skills, the employees could perform better. Among the predictors investigated, workload and skill discretion showed a significant effect on job performance. The recommendation for future research was also discussed and highlighted.